Influence of medium constituents on the biosynthesis of cephalosporin-C - Nigam, V.K.; Verma, R.; Kumar, A.; Kundu, S.; Ghosh, P. (My University, 2007)
Acremonium chrysogenum NCIM 1069 was used for the biosynthesis of cephalosporin-C (CPC) in batch mode of cultivation. The effect of different medium constituents for better yield of CPC was thoroughly investigated. From the results of the fermentation, it was found that ammonium sulphate as inorganic nitrogen source and methionine at the concentration of 0.4% are most suitable for higher yield of antibiotic. The variation in the C/N ratio on the biosynthesis of CPC showed that a C/N ratio of 8.0 is most suitable for maximum production of CPC.
Keywords: Acremonium chrysogenum; Batch fermentation; Cephalosporin-C; Methionine; Stirred tank bioreactor